Pandemi Corona Terhadap Saham Syariah Indonesia - Muhammad Al Faridho (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2021)
In 2020, the world faced the corona virus pandemic, which can threaten the economy aspect of every country. There are many countries end up experiencing recession, including Indonesia. This study tries to test the effect of the corona pandemic on the Jakarta Islamic Index (JII) stock price, simultaneously and partially. The result shows the stock prices that are included in the Jakarta Islamic Index (JII), simultaneously for three quarters, significantly affected by the corona pandemic. Partially, not all issuers are affected by this pandemic. It can be seen that the issuers affected in the Q1 range are ADRO, INCO, SCMA, UNVR, in the Q2 are ADRO, ASII, BTPS, ERAA, ICBP, INDF, INTP, MDKA, MNCN, PTBA, SCMA, SMGR and UNVR, while in the Q3 are ANTM, ERAA, MDKA, PGAS, TPIA.